DISCRETE CHOICE EXPERIMENT FOR STATE ISLAMIC UNIVERSITY QUALITY IMPROVEMENT - Suteja Wira Dana Kusuma; Muhammad Zaky; Moh. Nadhir Mua'mmar (Universitas Airlangga, 2026)
This study aims to explore the manner in which students at Indonesian State Islamic Universities (PTKIN) value different aspects of quality improvement in higher education and what they would be willing to pay in exchange for an increase in tuition fees. This is an important topic as PTKIN need to find an approach to improve their institutional quality without losing their attractiveness for students due to increased tuition fees. The value that students place on three critical dimensions of university quality: administrative staff quality, campus facilities, and lecturer quality. We use a Discrete Choice Experiment (DCE) to estimate the students' preferences. We apply a two-class latent class logit model to capture differences in the preference patterns among students. Finally, we estimate the students' willingness-to-pay (WTP) based on a comparison between the attribute coefficients and the tuition fee coefficient. Our results demonstrate that there are two types of students. One group attaches more value to administrative services and facilities and is sensitive towards changes in tuition fees. The other group values lecturer quality more and has a relatively higher threshold for paying extra tuition fees when those fees contribute to academic quality. In contrast, our estimates show that the overall WTP amounts are quite low, which shows that students do not have much room for tuition fee increases. The results suggest that students might react differently to one-size-fits-all approaches towards tuition fee levels and quality improvement.